Experimental Analysis of Cooling Fluid Temperature Effects on the Performance of a Thermoelectric Generator (TEG) Integrated with Heat Sink - Hermawan, Indra; Lian Galed S. (JOURNAL OF MECHANICAL ENGINEERING MANUFACTURES MATERIALS AND ENERGY, 2025)
This study aims to experimentally analyze the effect of coolant temperature on the performance of a Thermoelectric Generator (TEG) combined with a finned aluminum heatsink. The TEG operates based on the Seebeck effect, where a temperature difference between the hot and cold sides generates electrical energy. The experiment employed six SP-1848 TEG modules arranged in series and mounted on a heatsink partially immersed in static water as a cooling fluid. Measurements were taken every 300 seconds for a total of 3600 seconds, monitoring parameters such as hot side temperature (Th), coolant temperature (Tc), voltage, and current, as well as calculated power and efficiency. The results showed that the increasing exposure time to solar heat gradually raised Th, while Tc increased more slowly. The resulting temperature difference (ΔT) directly contributed to an increase in electrical power output of more than 0.005 W, and TEG efficiency exceeding 14%. This study highlights the importance of thermal management through heatsinks and coolant fluids in optimizing TEG performance, particularly in small-scale renewable energy applications.